An Optimal Peer Group Selection Strategy for Multiples-Based Modelling in the South African Equity Market - Nel, WS (Journal of Economics and Behavioral Studies, 2015)
Although peer group selection is a key consideration when performing multiples-based valuations, there is a lack of theoretical guidance on an optimal peer group selection strategy in emerging markets. Principal Component Analysis-based biplots and correlation monoplots are used to assess the valuation performance of multiples whose peer groups are based on either industry classification or valuation fundamentals. The evidence suggests that multiples whose peer groups are based on valuation fundamentals outperform multiples whose peer groups are based on industry classifications, with a combination of valuation fundamentals Rg and RoE emerging as the optimal peer group variable. The evidence suggests that an optimal choice of peer group variable could secure an increase in valuation precision of as much as 41.77%.